Comparison of thermodynamic models for ice accretion on airfoils. Issue 5 (8th May 2018) - Lavoie, Pierre; Pena, Dorian; Hoarau, Yannick; Laurendeau, Eric
Abstract : Purpose: This paper aims to assess the strengths and weaknesses of four thermodynamic models used in aircraft icing simulations to orient the development or the choice of an improved thermodynamic model. Design/methodology/approach: Four models are compared to assess their capabilities: Messinger, iterative Messinger, extended Messinger and shallow water icing models. They have been implemented in the aero-icing framework, NSCODE-ICE, under development at Polytechnique Montreal since 2012. Comparison is performed over typical rime and glaze ice cases. Furthermore, a manufactured geometry with multiple recirculation zones is proposed as a benchmark test to assess the efficiency in runback water modeling and geometry evolution. Findings: The comparison shows that one of the main differences is the runback water modeling. Runback modeling based on the location of the stagnation point fails to capture the water film behavior in the presence of recirculation zones on airfoils. However, runback modeling based on air shear stress is more suitable in this situation and can also handle water accumulation while the other models cannot. Also, accounting for the conduction through the ice layer is found to have a great impact on the final ice shape as it increases the overall freezing fraction. Originality/value: This paper helps visualize the effect of different thermodynamic models implemented in the same aero-icing framework. Also, the use of a complex manufactured geometry highlights weaknesses not normally noticeable with classic ice accretion simulations. To help with the visualization, the ice shape is presented with the water layer, which is not shown on typical icing results.